Antioxidative Potentials of Incretin-Based Medications: A Review of Molecular Mechanisms. (28th April 2021) - Yaribeygi, Habib; Maleki, Mina; Sathyapalan, Thozhukat; Jamialahmadi, Tannaz; Sahebkar, Amirhossein
Abstract : Glucagon-like peptide 1 receptor agonists and dipeptidyl-peptidase 4 inhibitors are medications used for managing diabetes, mimicking the metabolic effects of incretin hormones. Recent evidence suggests that these medications have antioxidative potentials in the diabetic milieu. The pathophysiology of most diabetic complications involves oxidative stress. Therefore, if incretin-based antidiabetic medications can alleviate the free radicals involved in oxidative stress, they can potentially provide further therapeutic effects against diabetic complications. However, the molecular mechanisms by which these medications protect against oxidative stress are not fully understood. In the current review, we discuss the potential molecular mechanisms behind these pharmacologic agents' antioxidative properties.